African development indicators - World Bank. (Washington, D.C. : International Bank for Reconstruction and Deve lopment / The World Bank, 2007)
Contains detailed economic, social, and environmental data for Afric an countries.
"World Bank software."
"Data on diskette with STARS retrieval system."
Also known as: ADI.
Contains latest version of STARS (Socioeconomic Timeseries Access an d Retrieval System) software.
Description based on: 1992-93; title from disk label.
Also issued in print.
Keywords: Economic indicators -- Africa -- Statistics -- Databases; Social indicators -- Africa; Africa -- Economic conditions -- 1960- -- Statistics -- Databases; Africa -- Social conditions -- 1960- -- Statistics -- Databases